A facile strategy for preparing silk fabrics with rapid photothermal antibacterial ability. (October 2022) - Yan, Biaobiao; Ren, Yiwen; Ding, Shulin; Zhou, Man; Cui, Li; Yu, Yuanyuan; Wang, Qiang; Xu, Bo; Wang, Ping
Abstract: Herein, the photothermal antibacterial fabric was successfully prepared, via combinedly pretreating silk with chitosan quaternary ammonium salt (HACC), followed by binding of polystyrene sulfonate (PSS) and efficient deposition of polythiophene (PEDOT). Impressively, the graft modified fabric has outstanding photothermal conversion capability, and surface temperature can reach 107.5 °C when irradiated at a light intensity of 200 mW/cm 2 for 1 min. Utilizing the excellent photothermal performance of PEDOT:PSS system, the graft modified fabric exhibits nearly 100% resistance to E. coli and S. aureus . And it still maintains 99.79% and 93.09% antibacterial performance against both bacteria after ten repeated standard washes. The present work provides a simple and efficient alternative to solve the problem of medical textile reuse. Graphical abstract: Image 1 Highlights: HACC pretreatment promotes the deposition of PEDOT:PSS on silk fibers. PEDOT-modified fabric exhibits rapid photothermal antibacterial ability. The composite fabric remains stable photothermal properties after cyclic washing.